Study of prognostic clinical factors affecting mortality rate in patients with severe covid_19 at Tishreen University Hospital - الحماده أحمد; محمد الخير; مالك حجازية (Latakia University Journal -Medical Sciences Series, 2023)
Background: Mortality rates are high among hospitalized patients with COVID-19, especially in those on the ICU. Previous studies have reported that older patients may experience worse outcome(s) after infection with severe acute respiratory syndrome coronavirus-2 than younger individuals .This study aimed to identify potential clinical risk factors for mortality in patients with coronavirus disease 2019 (COVID-19) on admission, which may help identify those with poor prognosis at an early stage.. Methods: : In this retrospective cohort study, we reviewed the health records of patients with COVID-19 who were admitted from August -2020–JULY- 2021, Subjects with confirmed reverse transcriptase-polymerase chain reaction (RT-PCR) of the nasopharyngeal swab for severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) were included. We collected data related to demographics, comorbidity and outcome of hospitalization. Outcome was measured based on whether the patient was discharged home or died during hospitalization. Results: 200 patients with severe COVID-19 on admission were included and divided into discharge group 143 (71.5%) and death group 57 (28.5%). Mean age was 64.57±12.8 years(rank 28–93) with 52.5% over 65 years. The majority of patients were male (66%) . On multiple regression analysis, increasing odds of mortality during hospitalization was associated with older age (Relative Risk[RR]1.6; 95% confidence interval [CI], 0.9-8.4 ; p < 0.01) ,Smoking (Relative Risk[RR]5.4; 95% confidence interval [CI], 2.4-12.2 ; p < 0.0001).Cancer (Relative Risk[RR]20.8; 95% confidence interval [CI], 4.5-31.6 ; p < 0.0001) . hypoxia (Relative Risk[RR]19; 95% confidence interval [CI], 5.6-27.3 ; p < 0.0001) .Needs for Mechanical Ventilation (Relative Risk[RR]9; 95% confidence interval [CI], 2.3-18.7 ; p < 0.0001) Conclusions: On admission; older age , Smoking , Cancer, hypoxia , Needs for Mechanical Ventilation were associated with increased mortality rate in patients hospitalized for COVID-19.